Analysis of errors of commission for a CE type plant with the advanced control room in the full power condition. (July 2017) - Yang, Jaemin; Kim, Taewan; Kim, Jonghyun
Highlights: Errors of commission (EOCs) are identified and quantified for a CE type plant at full power. An approach to combine the CESA and MDTA methods is suggested. As a result, 12 EOCs have been analyzed and the impact on the PSA has been discussed. Abstract: This study analyzes errors of commission (EOCs) committed by operators of an Combustion Engineering (CE) type plant with the advanced control room during full power operation, by using the Commission Errors Search and Assessment (CESA) and Misdiagnosis Tree Analysis (MDTA) methods. The contribution of EOCs to plant safety is significant in the digital control room of the reference plant, where the cognitive behavior of an operator plays more important role in the control than in the analog control room. In this study, the CESA and MDTA methods are applied to the identification and quantification of EOCs, respectively. This study chooses eight initiating events that account for approximately 90% of the total core damage frequency (CDF) in the full power condition of the reference plant. As a result of applying the CESA method, twelve EOCs are identified along with the accident sequence groups. Then, the probabilities of those EOCs are quantified through the MDTA method. Finally, this study discusses the effect of EOCs on system failure probability, as well as the necessity of considering EOCs in the probabilistic safety assessment (PSA) of the reference plant.